Policy Harmony or Dissonance? Investigating Alignment in Indonesia's Multi-Level Governance System - Ningrum , Sinta; Dwiputri , Dinar Afina; Agus , Ridha; Fazarani , Farah; Roseline, Herlina (Journal of Ecohumanism, 2025)
Indonesia targets significant economic growth by 2045, mandating equitable development nationwide. This study analyzes the alignment of national, provincial, and city-level development plans and budgets, focusing on identifying policy gaps and fostering harmonization. We used a qualitative methodology to review relevant legislation and government documents and interviewed Bandung City officials and academics. Analysis revealed substantial discrepancies across planning documents – the National Medium-Term Development Plan (RPJMN), West Java's Provincial plan (RPJMD Regional), and Bandung City's local plan (RPJMD Local) – particularly in economic, infrastructure, and health sectors. Significant time lags between plan approvals, inconsistent program prioritization, and the influence of political promises on development planning were observed. Budget allocations frequently prioritized bureaucratic processes over direct community impact. Our findings highlight the critical need for enhanced intergovernmental coordination, stronger institutional mechanisms, and more transparent, data-driven decision-making to achieve development objectives. Weaknesses in intergovernmental consultation, institutional arrangements, and the influence of political factors hinder effective policy implementation. We propose institutional reforms and improved intergovernmental collaboration to strengthen integration and optimize budget allocation across all levels of government. This study offers crucial policy recommendations to overcome these challenges and accelerate Indonesia's equitable and sustainable development.